Impacts of omega-3 fatty acids intervention on immune functions and clinical outcomes in surgical gastric cancer patients: a systematic review and trial sequential meta-analysis - Han Yang Yue; Xue Ting Yang; Jian Cheng Zhang; Ping Zhou; Jue Xia He; Jun Zeng; Jun Ying Li; Hua Jiang (BMC Cancer)
Abstract Background Gastric cancer patients are vulnerable to postoperative complications. Omega-3 fatty acids may improve immune function and reduce postoperative complications. However, the impacts of omega-3 fatty acids intervention on immune function and clinical outcomes in gastric cancer patients are not clear. Methods Seven databases were retrieved: Cochrane Library, Embase, PubMed, Web of Science, China National Knowledge Infrastructure (CNKI), Wanfang, and Yiigle. Randomized controlled trials (RCTs) were included. The Revised Cochrane risk-of-bias tool (ROB 2) was used to assess the risk of bias of included RCTs. RevMan software was used for data synthesis. Subgroup analysis and sensitivity analysis were conducted to evaluate the stability of the results. Trial sequential analysis (TSA) was performed to explore the false-positive results and estimate the required information size (RIS). Results Thirty-two RCTs involving 2,404 gastric cancer patients were included. Compared with the control group, omega-3 fatty acids supplementation significantly decreased the incidence of infectious complication (RR = 0.42; 95% CI, [0.32, 0.54]; P<0.00001; I2 = 0%), shortened the length of hospital stay (MD=-1.27 days; 95% CI [-2.10, -0.45]; P = 0.002; I2 = 67%), and elevated the level of CD4+ T cell (MD = 4.96%; 95% CI, [3.49, 6.44]; P<0.00001; I2 = 84%). No significant difference was observed in in-hospital mortality between the two groups (RR = 0.54; 95% CI, [0.12, 2.42]; P = 0.42; I2 = 0%). Trial sequential analysis demonstrated that the conclusion on the primary outcome improvement is robust because it reached the required sample size and excluded the presence of false positive results. The GRADE assessment indicated moderate certainty of outcomes for infectious complications, CD4+ T cells, CD8+ T cells, and CD4/CD8 ratio, and low certainty for in-hospital mortality and length of hospital stay. Conclusions Omega-3 fatty acids intervention is associated with reduction of the occurrence of infectious complications in gastric cancer patients and may improve immune function. Trial registration The protocol for our meta-analysis and systematic review was registered and recorded in PROSPERO (registration no. CRD42024562523).